Rural household resilience to food insecurity in Mekiet district, Ethiopia - Dessie, Tadsual Asfaw; Demsie, Birhan Sisay (Frontiers in Sustainable Food Systems, 2024)
Introduction Food insecurity remains a global issue and a top national priority in Ethiopia. However, it continues to pose a serious challenge in rural areas. Therefore, this study investigated household resilience to food insecurity among rural residents in Mekiet district. Methods A cross-sectional research design was used, focusing on two agroecological zones of Mekiet district—lowland and midland—involving 228 respondents. The study employed both quantitative and qualitative approaches. Multistage sampling techniques were employed to select the sample households, and factor analysis was employed to analyze the data. Results and discussion The results from the factor analysis using the TANGO approach showed that the latent variables of absorptive and adaptive capacities had factor loadings of 0.98 and 0.79, respectively. On the other hand, transformative capacity showed a negative loading (−0.78), with all variables being statistically significant. The mean household resilience capacity index was 0.51. The variables of absorptive and adaptive capacities were positively associated with household resilience capacity, while transformative capacity exhibited a strong negative association. All factor loadings were significant, exceeding the recommended absolute value of 0.364 for sample sizes of 200 or more. Additionally, these variables were also highly correlated with resilience capacity. The study recommends that resilience programs be implemented at district, community, and household levels to enhance resilience to food insecurity.